Analysis of the Impact of Tourism Development on Economic and Social Culture Community Aspects - Zulkifli, Zulkifli; Yalumalai, Ravivarman (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
Abstract Batu Caves is a sacred spot for Hindu people in Kuala Lumpur. It was initially only an ordinary cave which then was built an iconic statue in front of the cave that attract tourists to come there. A statue of the Muruga God which has 42.7 meters (140 fts) tall has been launched in January 2006, attracting travelers from various parts of the world. The Malaysian government continues to develop the construction in the Batu Caves area. The construction development in each process will have the impacts, therefore there is a need of research on these impacts in order to avoid and reduce negative impacts and encourage positive impacts. This research process uses descriptive research method using a qualitative approach. The focus in this study is the implementation of tourism industrial development in it includes the development of tourist objects and attractions, infrastructures, marketing and promotion of tourism, and the development of human resources. The next focus is the impact on the economic and socio-cultural conditions of the community due to the development of tourism and previous conditions. The results show that development of construction continues to be carried out in terms of both physical and quality human resources. This tourism progress is able to improve the economic quality of the community, especially around Selangor Malaysia. Even the Thaipusam celebration has attracted 1.5 million adherents and made this celebration one of the largest meetings in 2007 in world history.